Tratamento da informação nos anos iniciais: contribuições do PIBID para professores e alunos - VILHENA, Vera Débora Maciel (2020)
This research focuses directly on the training of teachers and students about the problem of the teaching and learning of construction and data analysis charts and tables in the early grades of elementary school held under the Institutional Program Initiation to Teaching Scholarship ( PIBID). Consider the suggestion of the National Curriculum Parameters ( PCN ) concerning the treatment of information as well as the state school curriculum proposal that led us to do something more for teachers and students of the school in terms of reading, interpreting , analyzing and organizing data , variables considered essential for both teachers and learners . The investigation included workshops on information addressed to 16 teachers in a public school , and a class of 30 students of the 5th year of elementary school , which occurred from March 2012 to August 2013 treatments. The results point to the resourcefulness of teachers and students in relation to reading, construction and interpretation of graphs. Both knew how to seize the opportunity that stock PIBID gave them, because all the teachers involved in the workshops go by math class. Students study subjects had good performance in the suggested activities and Provinha Brazil . The information processing with concrete materials helped greatly in learning the technique and understanding of the importance of this study in school programs.